Spectroscopic Evolution in Ice Analogs of Trans-Neptunian Objects Exposed to Ionizing Radiation. I. Visible Reflectance Spectra and Colors - Chaojiang Zhang; Jia Wang; Andrew M. Turner; Leslie A. Young; Ralf I. Kaiser (The Astrophysical Journal Supplement Series)
Trans-Neptunian objects (TNOs) exhibit a color diversity containing a wealth of clues for understanding complex compositions and the formation history of our solar system. The origin of this wide color distribution is still uncertain, but it is likely due to surface ice exposed to ionizing radiation at various levels. Here, we present the spectroscopic evolution of visible reflectance, spectral slopes, and colors from TNO surface ice analogs processed by Galactic cosmic-ray proxy. This study provides compelling evidence that irradiated carbon-containing molecular ices show notable reddening in their visible reflectance spectra. The spectral slopes of processed water ices are neutral and independent of the radiation dose, whereas those of ammonia decrease with the increasing radiation dose. When the carbon-containing molecules are mixed with water and ammonia, the reddening process is found to be neutralized. The irradiation experiments at different temperatures demonstrate that the irradiation temperature could control the reddening efficiency of ices containing carbon and oxygen. For example, the color slopes of pure methanol and carbon dioxide ices significantly increase when the irradiation temperature is 40 K, but there is almost no change at 10 K. This indicates that the color diversity of TNOs can be influenced not only by different levels of radiation exposure but also by varying irradiation temperatures. The data in the current study provide new insights into the influence of initial composition, radiation dose, and irradiation temperature on the color diversity of TNOs, which supply important information for cataloging their surface compositions.